2002
DOI: 10.1074/jbc.m206379200
|View full text |Cite
|
Sign up to set email alerts
|

The Myostatin Propeptide and the Follistatin-related Gene Are Inhibitory Binding Proteins of Myostatin in Normal Serum

Abstract: Myostatin, also known as growth and differentiation factor 8, is a member of the transforming growth factor ␤ superfamily that negatively regulates skeletal muscle mass (1). Recent experiments have shown that myostatin activity is detected in serum by a reporter gene assay only after activation by acid, suggesting that native myostatin circulates as a latent complex (2). We have used a monoclonal myostatin antibody, JA16, to isolate the native myostatin complex from normal mouse and human serum. Analysis by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
363
2
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(384 citation statements)
references
References 42 publications
11
363
2
8
Order By: Relevance
“…A representative Western blot for myostatin is provided and revealed a band at approximately 15 kD, consistent with the secreted form of myostatin (Hill et al, 2002;Zimmers et al, 2002). We found that myostatin protein levels tended to be increased in the serum of COPD group compared with that of the group of healthy controls ( Fig.…”
Section: Myostatin Levels Are Increased In Copd Patientsmentioning
confidence: 69%
“…A representative Western blot for myostatin is provided and revealed a band at approximately 15 kD, consistent with the secreted form of myostatin (Hill et al, 2002;Zimmers et al, 2002). We found that myostatin protein levels tended to be increased in the serum of COPD group compared with that of the group of healthy controls ( Fig.…”
Section: Myostatin Levels Are Increased In Copd Patientsmentioning
confidence: 69%
“…Although such cleavage is sufficient for activating most TGFβ-like proteins (Hogan, 1996), prototypical family members TGFβ 1-3 remain noncovalently bound to their cleaved prodomains in latent complexes (Massague, 1998). More recently it has been demonstrated that GDF8 and 11, which share ~90% sequence identity in their mature regions (Gamer et al, 1999;Ge et al, 2005;Nakashima et al, 1999), are also noncovalently bound to their respective prodomains in latent complexes (Ge et al, 2005;Hill et al, 2002;Lee and McPherron, 2001;Wolfman et al, 2003) (Fig. 5B).…”
Section: Growth and Differentiation Factors 8 And 11 (Gdfs 8 And 11)mentioning
confidence: 99%
“…5B). Secreted by myocytes, GDF8, also known as Myostatin, is an important negative regulator of skeletal muscle growth (Hill et al, 2002;Lee and McPherron, 2001;McPherron et al, 1997), whereas GDF11, secreted by mature neurons, serves a comparable function in inhibiting neurogenesis (Wu et al, 2003). GDF11 also appears to play roles in anterior-posterior patterning of the axial skeleton (McPherron et al, 1999).…”
Section: Growth and Differentiation Factors 8 And 11 (Gdfs 8 And 11)mentioning
confidence: 99%
“…Secreted by the skeletal muscle, myostatin is found in an active unbound (free) form, or bound to its own propeptide, or separate peptides such as follistatin, or follistatin‐related gene (FLRG; Hill et al. 2002; Amthor et al. 2004; Gilson et al.…”
Section: Introductionmentioning
confidence: 99%